A Journey on Extracellular Vesicles for Matrix Metalloproteinases: A Mechanistic Perspective - Thuault, Sylvie; Ghossoub, Rania; David, Guido; Zimmermann, Pascale (Frontiers in Cell and Developmental Biology, 2022)
Matrix metalloproteinases (MMPs) are key players in matrix remodeling and their function has been particularly investigated in cancer biology. Indeed, through extracellular matrix (ECM) degradation and shedding of diverse cell surface macromolecules, they are implicated in different steps of tumor development, from local expansion by growth to tissue invasion and metastasis. Interestingly, MMPs are also components of extracellular vesicles (EVs). EVs are membrane-limited organelles that cells release in their extracellular environment. These ‘secreted’ vesicles are now well accepted players in cell-to-cell communication. EVs have received a lot of interest in recent years as they are also envisioned as sources of biomarkers and as potentially outperforming vehicles for the delivery of therapeutics. Molecular machineries governing EVs biogenesis, cargo loading and delivery to recipient cells are complex and still under intense investigation. In this review, we will summarize the state of the art of our knowledge about the molecular mechanisms implicated in MMP trafficking and secretion. We focus on MT1-MMP, a major effector of invasive cell behavior. We will also discuss how this knowledge is of interest for a better understanding of EV-loading of MMPs. Such knowledge might be of use to engineer novel strategies for cancer treatment. A better understanding of these mechanisms could also be used to design more efficient EV-based therapies.